ChemInform Abstract: Antiinflammatory Activity of a Novel Acetylene Isolated from the Roots of Angelica tenuissima NAKAI. Issue 46 (October 2016) - Choi, Hyun Gyu; Choi, Hyukjae; Lee, Jeong‐Hyung; Min, Byung Sun; Kim, Jeong Ah
Abstract: The novel acetylene (I) shows potent inhibitory activity against LPS‐induced NO production as well as strong inhibitory activities against iNOS and COX‐2.